GNS561, a clinical-stage PPT1 inhibitor, is efficient against hepatocellular carcinoma via modulation of lysosomal functions. Issue 3 (4th March 2022) - Brun, Sonia; Bestion, Eloïne; Raymond, Eric; Bassissi, Firas; Jilkova, Zuzana Macek; Mezouar, Soraya; Rachid, Madani; Novello, Marie; Tracz, Jennifer; Hamaï, Ahmed; Lalmanach, Gilles; Vanderlynden, Lise; et al.
ABSTRACT: Hepatocellular carcinoma is the most frequent primary liver cancer. Macroautophagy/autophagy inhibitors have been extensively studied in cancer but, to date, none has reached efficacy in clinical trials. In this study, we demonstrated that GNS561, a new autophagy inhibitor, whose anticancer activity was previously linked to lysosomal cell death, displayed high liver tropism and potent antitumor activity against a panel of human cancer cell lines and in two hepatocellular carcinoma in vivo models. We showed that due to its lysosomotropic properties, GNS561 could reach and specifically inhibited its enzyme target, PPT1 (palmitoyl-protein thioesterase 1), resulting in lysosomal unbound Zn 2+ accumulation, impairment of cathepsin activity, blockage of autophagic flux, altered location of MTOR (mechanistic target of rapamycin kinase), lysosomal membrane permeabilization, caspase activation and cell death. Accordingly, GNS561, for which a global phase 1b clinical trial in liver cancers was just successfully achieved, represents a promising new drug candidate and a hopeful therapeutic strategy in cancer treatment. Abbreviations : ANXA5:annexin A5; ATCC: American type culture collection; BafA1: bafilomycin A1 ; BSA: bovine serum albumin; CASP3: caspase 3; CASP7: caspase 7; CASP8: caspase 8; CCND1: cyclin D1; CTSB: cathepsin B; CTSD: cathepsin D; CTSL: cathepsin L; CQ: chloroquine; iCCA: intrahepatic cholangiocarcinoma; DEN: diethylnitrosamine; DMEM: Dulbelcco's modified Eagle medium; FBS: fetal bovine serum; FITC: fluorescein isothiocyanate; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HCC: hepatocellular carcinoma; HCQ: hydroxychloroquine; HDSF: hexadecylsulfonylfluoride; IC50 : mean half-maximal inhibitory concentration; LAMP: lysosomal associated membrane protein; LC3-II: phosphatidylethanolamine-conjugated form of MAP1LC3; LMP: lysosomal membrane permeabilization; MALDI: matrix assisted laser desorption ionization; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MKI67: marker of proliferation Ki-67; MTOR: mechanistic target of rapamycin kinase; MRI: magnetic resonance imaging; NH4 Cl: ammonium chloride; NtBuHA: N-tert-butylhydroxylamine; PARP: poly(ADP-ribose) polymerase; PBS: phosphate-buffered saline; PPT1: palmitoyl-protein thioesterase 1; SD: standard deviation; SEM: standard error mean; vs, versus; Zn 2+ : zinc ion; Z-Phe: Z-Phe-Tyt(tBu)-diazomethylketone; Z-VAD-FMK: carbobenzoxy-valyl-alanyl-aspartyl-[O-methyl]- fluoromethylketone.